Knowledge about juvenile idiopathic arthritis-associated uveitis: more frequent reminders are associated with higher patient and family uveitis knowledge - Ashley M. Cooper; Elaine R. Flanagan; Tova Ronis; Baruch Goldberg; Ashley K. Sherman; Chelsey Smith; Gary N. Holland; for the CARRA Uveitis Workgroup (BMC, 2021)
Abstract Background Chronic anterior uveitis is a sight-threatening complication of juvenile idiopathic arthritis (JIA) and a primary contributor to long-term morbidity in people with JIA. Levels of knowledge about uveitis among JIA patients and their parents are unknown. A survey of JIA patients and parents was conducted to assess knowledge about uveitis complications and recommended screening. Methods A survey was developed consisting of six demographic questions, six arthritis/uveitis history questions, and nine uveitis knowledge questions. The survey was administered to JIA patients age 14 and older and parents of patients with JIA at three pediatric rheumatology practices and online through the Patients, Advocates, and Rheumatology Teams Network for Research and Service (PARTNERS) network. ANOVA, chi-square and Fisher's exact tests were used to look for relationships between survey questions and demographic variables. Results Thirty-three patients and 111 parents completed the survey. Overall, 17.4% reported a history of uveitis, and 89.6% had heard of uveitis. The mean composite knowledge score was 6.46 ± 2.6 out of 9. Patients and parents with a history of uveitis had higher composite knowledge scores than their counterparts without a uveitis history (p = 0.01 and p < 0.01, respectively). Parents whose rheumatologist reminded them about eye exams at every visit had higher knowledge of the risk of blindness (p = 0.04), the risk for uveitis when arthritis is controlled (p = 0.02), the need for ongoing eye exams when off of medications (p = 0.01), and had a higher overall score (p = 0.02) than those who were reminded at some visits or not at all. Conclusions JIA patients and parents report variable levels of knowledge regarding uveitis complications and recommended screening. Frequent discussion between the rheumatology provider and family about uveitis screening is associated with higher uveitis knowledge. Incorporating detailed and frequent education about uveitis into rheumatology clinic appointments may improve early uveitis detection and visual outcomes.